Performance Research of Air-conditioning Heat Exchanger Without Heat Contact Resistance - Wang Rui; Feng Chaoqing; Wang Yichun (Zhileng xuebao)
Combined the without heat contact resistance technology with different corrugated fins, the new kinds of fin has been developed. The surface heat transfer coefficient and friction coefficient of fins was calculated by CFD software in order to find the different between sharp corner corrugated fins and rounded corner corrugated fins. The sample of heat exchanger was made and the performance was tested in wind tunnel experimental system. Compared the simulation and experiment result, we found that they have good consistency and the errors between them are less than 10%. The simulation result can reflect the real heat transfer situation between the fins of exchanger. Evaluation of heat transfer enhancement was adopted. The result showed that the DEC always bigger than 1 in different wind speed, so the performance of sharp corner corrugated fins is better than rounded corner corrugated fins.